At the Surface of Romantic Interiority: Joanna Baillie’s Orra - Murray, Julie (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2009)
This essay examines Joanna Baillie’s 1812 play, Orra, in order to interrogate the longstanding opposition between personification and romantic interiority. Since Wordsworth, the personified abstraction has been considered anathema to romantic conceptions of passionate or lyrical interiority. Drawing on recent critical discussions of the close relationship between passion, personification, and personhood, I suggest that Baillie’s play represents deep interiority via the most un-Wordsworthian figure imaginable: personified passion. In so doing, she employs a seemingly archaic, extravagant figure in order to stage the deep, unknowable interiors which are the ostensible hallmark of the modern individual.